High Light Intensity Leads to Increased Peroxule-Mitochondria Interactions in Plants - Jaipargas, Erica-Ashley; Mathur, Neeta; Bou Daher, Firas; Wasteneys, Geoffrey O.; Mathur, Jaideep (Frontiers in Cell and Developmental Biology, 2016)
Peroxules are thin protrusions from spherical peroxisomes produced under low levels of reactive oxygen species (ROS) stress. Whereas stress mitigation favours peroxule retraction, prolongation of the ROS stress leads to the elongation of the peroxisome into a tubular form. Subsequently, the elongated form becomes constricted through the binding of proteins such as dynamin related proteins 3A and 3B and eventually undergoes fission to increase the peroxisomal population within a cell. The events that occur in the short time window between peroxule initiation and the tubulation of the entire peroxisome have not been observed in living plant cells. Here, using fluorescent protein aided live-imaging, we show that peroxules are formed after only 4 minutes of high light (HL) irradiation during which there is a perceptible increase in the cytosolic levels of hydrogen peroxide. Using a stable, double transgenic line of Arabidopsis thaliana expressing a peroxisome targeted YFP and a mitochondrial targeted GFP probe, we observed sustained interactions between peroxules and small, spherical mitochondria. Further it was observed that the frequency of HL-induced interactions between peroxules and mitochondria increased in the Arabidopsis anisotropy1 mutant that has reduced cell wall crystallinity and where we show accumulation of higher H2O2 levels than wild type plants. Our observations suggest a testable model whereby peroxules act as interaction platforms for ROS-distressed mitochondria that may release membrane proteins and fission factors. These proteins might thus become easily available to peroxisomes and facilitate their proliferation for enhancing the ROS-combating capability of a plant cell.